Ethical Problems Related to Physicians’ Responsibility of Notification in Turkey - Çekin, Necmi; Gülmen, Mete Korkut; Hilal, Ahmet; Salaçin, Serpil (The Bulletin of Legal Medicine, 1999)
The article 530 of the Turkish Penal Code (TPC) obliges the medical practitioners to notify the officials when they notice a finding of assault against their patients without their consent if this will not lead to a follow-up questioning of the patient. One of the important questions raised in this matter is; how the physicians will play the decision-making role in the follow-up questioning of their patients and reconcile this with the educational curriculum that had been given to them during the university years. The spirit of the law seems to be that it has the aim to protect the victim, and to investigate the crime and the criminal. However, there is a contradiction here with the ethical concepts such as secrecy, loyalty, confidentiality etc. when noticing the officials without the consent or even with the objection of the patient. We believe that the article 530 of the Turkish Criminal Law should be discussed and reconstructed as regards the consent of the patient in special conditions such as torture, family violence etc.Key words: Responsibility of Notification (TCL, art. 530), Confidentiality (TCL, art. 198), Patient Rights, The Right of Access to Treatment, Forensic Medicine.
Keywords: responsibility of notification; confidentiality; patient rights; the right of access to treatment; forensic medicine; turkish penal code